PSYCHOSOCIAL FACTORS AS RISK FACTOR IN SUICIDAL POISONING: A CROSS-SECTIONAL STUDY - Raut, Asawari; Shaj, Kavya; Pawar, Atmaram (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Suicide is known to be a phenomenon in low-, middle-, and high-income countries and occurs in all sociodemographic groups. It ranges from acute to fatal lethal attempts which occur in the context of a social crisis. Deliberate self-poisoning for suicide is a growing public health concern with frequent emergency department admissions. An epidemiological surveillance is essential for every region to understand the pattern, underlying psychological factors, and the scope of preventive measures. Methods: The 2-year retrospective study describes the epidemiology and influencing factors of suicides by self-poisoning in patients admitted to a Government Hospital and a Teaching Hospital in Pune, Maharashtra, from January 1, 2014 to December 31, 2015. Result: Out of 1010 poisoning cases reported, 539 were suicidal self-poisoning. Significantly males more than females were brought to the hospitals due to deliberate self-poisoning (1:0.86, Ï‡2=38.05; p<0.001). The age group most recorded was 20-35 years (67.7%). Psychosocial factors were associated with increased risk of suicidal self-poisoning attempts (risk ratio 4.76, 95% confidence interval 4.07-5.57; p<0.001). Psychosocial factors were interpersonal conflict (52.4%), stress (30.4), dissatisfaction in life (6%), and alcoholism or mental disorders (11.1%). Household and agricultural products (71.8%) were the popular choices of the toxic agent in self-poisoning with phenols (20%) being the most common. 19 cases (3.5%) were severe, out of which 15 cases lead to death (2.8% mortality). Conclusion: There is an urgent need to develop and implement preventative and treatment strategies for high-risk groups attempting suicide by self-poisoning.